Lathrolestes bipunctatus Bridgman 1886 - Reshchikov, Alexey (Zenodo, 2015)
Lathrolestes bipunctatus (Bridgman, 1886) Figs. 18, 32, 49–51. Grypocentrus bipunctatus Bridgman, 1886: 358 –359. Holotype ♀, NCMK [examined]. Type locality: UK (Wimbledon, Surrey). Material: 1♀, 1♂, DENMARK, Saltrup, 18.ix.1892, ZMUC; 1♀, NORWAY, Hordaland, Eidfjord, Rjoto, lok. D, 23.VII.1968, leg. T. Nielsen et al., (ZMBN); 2♂, RUSSIA, Sverdlovsk Oblast, Polevskoy, ex. Fenusini on Rosa , 4– 11.viii.1986, leg. Zinovev, ZIN; 1♀, SWEDEN, Uppland, Djurgården, leg. R.Malaise, NHRS; 2♀, SWEDEN, Värmland, Munkfors kommun, Ransäter, Rudstorp, Sandy railway embankment through pasture-land. N66°36.454´E13°69.030´(=TrapID 1002), 12.viii–24.viii.2005 (=coll. event ID 1379), leg. SMTP, NHRS. Diagnosis . This species differs from other species of the genus by the following character states: 1) face and clypeus separated by a distinct transverse groove, 2) complete occipital carina, 3) reddish-yellow spots at upper part of temple, 4) dark coloration of hind femur, 5) propodeum with complete carinae. Distribution . Belarus, Denmark *, Finland, Germany, Norway, Poland, Russia (Murmansk Oblast, Sverdlovsk Oblast, Chita Oblast, Kamchatka Krai, Kunashir), Sweden (Uppland, Värmland), UK. Published as part of Reshchikov, Alexey, 2015, Review of North European species of the genus Lathrolestes (Hymenoptera, Ichneumonidae) with description of one new species from Öland (Sweden), pp. 1-47 in Zootaxa 4033 (1) on page 15, DOI:10.11646/zootaxa.4033.1.1, http://zenodo.org/record/289776